Brain hemorrhage after endovascular reperfusion therapy of ischemic stroke: a threshold-finding whole-brain perfusion CT study. Issue 1 (January 2017) - Renú, Arturo; Laredo, Carlos; Tudela, Raúl; Urra, Xabier; Lopez-Rueda, Antonio; Llull, Laura; Oleaga, Laura; Amaro, Sergio; Chamorro, Ángel
Endovascular reperfusion therapy is increasingly used for acute ischemic stroke treatment. The occurrence of parenchymal hemorrhage is clinically relevant and increases with reperfusion therapies. Herein we aimed to examine the optimal perfusion CT-derived parameters and the impact of the duration of brain ischemia for the prediction of parenchymal hemorrhage after endovascular therapy. A cohort of 146 consecutive patients with anterior circulation occlusions and treated with endovascular reperfusion therapy was analyzed. Recanalization was assessed at the end of reperfusion treatment, and the rate of parenchymal hemorrhage at follow-up neuroimaging. In regression analyses, cerebral blood volume and cerebral blood flow performed better than Delay Time maps for the prediction of parenchymal hemorrhage. The most informative thresholds (receiver operating curves) for relative cerebral blood volume and relative cerebral blood flow were values lower than 2.5% of normal brain. In binary regression analyses, the volume of regions with reduced relative cerebral blood volume and/or relative cerebral blood flow was significantly associated with an increased risk of parenchymal hemorrhage, as well as delayed vessel recanalization. These results highlight the relevance of the severity and duration of ischemia as drivers of blood-brain barrier disruption in acute ischemic stroke and support the role of perfusion CT for the prediction of parenchymal hemorrhage.